Association between Helicobacter pylori and otitis media with effusion in children: A systematic review. (August 2020) - Du, Peiyu; Zong, Shimin; Wen, Yingying; Liu, Tianyi; Qu, Yanji; Li, Hao; Yu, Wenting; Wang, Enhao; Zhong, Yi; Xiao, Hongjun
Abstract: Background: Studies have shown that Helicobacter pylori ( H. pylori ) infection may be associated with the occurrence of otitis media with effusion (OME) in children. Objective: This is a systematic review of the relevant published literature to explore the relationship between H. pylori infection and OME in children. Method: Articles published before October 30, 2019 in the PubMed, Web of Science, Ovid, the China National Knowledge Infrastructure (CNKI) database, and Wanfang databases were retrieved. Articles were screened based on prespecified inclusion and exclusion criteria. Quality assessment was applied to the included studies. Data in the included studies were extracted and classified for qualitative analysis. Results: Ten studies, which enrolled a total of 397 cases and 334 controls, were included; all were case-control studies of varying quality. We summarized and compared H. pylori infections in different specimens from pediatric patients with OME. Due to the apparent heterogeneity between the included studies, meta-analysis was not appropriate, hence we carried out only a qualitative analysis. Conclusion: The detection rate of H. pylori in the middle ear, tonsil and gastric juice in children with OME was higher than that in children without OME. There is no clear and reliable conclusion as to whether there is a difference in the detection rate of H. pylori in adenoid specimens of children with or without OME. Eradication of H. pylori may improve symptoms of drug-resistant OME. Nevertheless, more studies of higher quality are needed to improve the conclusions.